2018
DOI: 10.3389/fpubh.2018.00309
|View full text |Cite
|
Sign up to set email alerts
|

Parental Intention to Support the Use of Computerized Cognitive Training for Children With Genetic Neurodevelopmental Disorders

Abstract: Children with genetic neurodevelopmental disorders (NDDs) such as Down syndrome, Prader-Willi syndrome, and Fragile X syndrome may show a range of cognitive impairments, including impairments in executive functions (EF). EF are related to general intelligence, academic achievement, and literacy and mathematical skills. EF deficits are linked to a variety of clinically and socially important behaviors. Therefore, methods for improving EF in children with NDDs could be beneficial. One method for improving EF is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The greater plasticity of the young brain could endorse the exploration of intervention strategies aimed at supporting the reorganization of the brain circuitry, possibly leading to more favourable developmental outcomes (Cioni et al, 2016;Inguaggiato et al, 2017). In the last two decades, numerous studies investigated the efficacy of cognitive treatments for children with neurodevelopmental disorders, with a large proportion of research in this area focusing on computerized approaches delivered at a distance (Corti et al, 2019(Corti et al, , 2020Linden et al, 2016;Linden et al, 2018;Lindsay et al, 2015;Novak & Honan, 2019;Resch et al, 2018;Robb et al, 2018). Cognitive training programs delivered remotely, falling under the wide category of telerehabilitation, have been found to diminish economical and time burden usually implied in traditional rehabilitation and to give patients the possibility to achieve high dose therapy, allowing the provision of treatments in the breaks from routine therapy or increasing the number of sessions administered in a given time frame (Corti et al, 2018;Myrhaug et al, 2014;Novak & Cusick, 2006;Sakzewski et al, 2014;Schmeler et al, 2009;Zampolini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater plasticity of the young brain could endorse the exploration of intervention strategies aimed at supporting the reorganization of the brain circuitry, possibly leading to more favourable developmental outcomes (Cioni et al, 2016;Inguaggiato et al, 2017). In the last two decades, numerous studies investigated the efficacy of cognitive treatments for children with neurodevelopmental disorders, with a large proportion of research in this area focusing on computerized approaches delivered at a distance (Corti et al, 2019(Corti et al, , 2020Linden et al, 2016;Linden et al, 2018;Lindsay et al, 2015;Novak & Honan, 2019;Resch et al, 2018;Robb et al, 2018). Cognitive training programs delivered remotely, falling under the wide category of telerehabilitation, have been found to diminish economical and time burden usually implied in traditional rehabilitation and to give patients the possibility to achieve high dose therapy, allowing the provision of treatments in the breaks from routine therapy or increasing the number of sessions administered in a given time frame (Corti et al, 2018;Myrhaug et al, 2014;Novak & Cusick, 2006;Sakzewski et al, 2014;Schmeler et al, 2009;Zampolini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Further, genetic syndromes, such as Down syndrome, Prader-Willis syndrome, Fragile X syndrome or Williams syndrome and others, can affect brain development even without macroscopic neuroanatomical alterations. Children with brain malformations or syndromes due to genetic origin may exhibit a constellation of symptoms, including motor, cognitive, affective and behavioural deficits (Boltshauser, 2004; Cornish et al, 2007; Costanzo et al, 2013; Fennell et al, 1999; Grieco et al, 2015; Lanfranchi et al, 2012; Mervis & John, 2010; Novak, 2014; Robb et al, 2018; Stadskleiv et al, 2018; Stadskleiv, 2020; Tavano & Borgatti, 2010; Vicari et al, 2002) which require clinical understanding and may benefit from the identification of tailored rehabilitation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that the AR version of the n-back test was rated as more engaging and having more stimulating graphics than the traditional version. Given that engagement with cognitive training is recognized as a key factor contributing to the effectiveness of such training (Robb et al, 2018), these findings suggest that AR and other related technologies could play a role in the effectiveness of cognitive training software.…”
Section: Discussionmentioning
confidence: 96%
“…Many studies demonstrate the potential of cognitive training to improve cognitive functions in healthy young adults (Tulbure & Siberescu, 2013), older adults (Anguera et al, 2013), children (Van Dongen-Boomsma et al, 2014), and even in clinical populations (Bahar-Fuchs et al, 2013; Robb et al, 2018). Even relatively short periods of computerized training can lead to significant improvements in the working memory and attention capacity of young healthy adults (Akter et al, 2015; Tulbure & Siberescu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Their clinical conditions may seriously hamper their social desirability, image, and status with deleterious outcomes on their quality of life [1][2][3][4]. To tackle this issue, one may refer to assistive technology-based rehabilitative programs (AT) [5,6]. Thus, AT-based interventions include any technological aid combined with specific tools and/or devices with adapted software capable of reducing and minimizing the existing gap between the individual abilities and the environmental requests [7][8][9][10].…”
Section: Check For Updatesmentioning
confidence: 99%